Combined Anterior Cruciate Ligament Arthroscopic Reconstruction and Lateral Tenodesis Using Iliotibial Band Augmented With Gracilis Tendon - Sylvain Aubret, M.D.; Christian Lutz, M.D.; François Batisse, M.D.; Emmanuel Lamglait, M.D.; Charles Casin, M.D.; William Van Hille, M.D. (Arthroscopy Techniques)
The iliotibial band autograft as a primary reconstruction graft for anterior cruciate ligament reconstruction was published by Hey-Groves et al. in the 1910s and popularized by MacIntosh et al. in 1970s using an over-the-top technique. The scientific community, however, lost interest in the procedure. Recently, anatomical and biomechanical studies on the anterolateral structures have renewed the scientific interest on extra-articular tenodesis. To obtain a larger intra-articular graft diameter and thus improve long-term results, we propose a modified version of the technique initially described. This article describes a technique that allows for a combined anterior cruciate ligament and anterolateral reconstruction using an iliotibial band autograft reinforced with a gracilis tendon autograft to increase the diameter.